EFEKTIVITAS PAMERAN JOB EXPO OLEH DINAS TENAGA KERJA KOTA PEKANBARU - Angelina Ambarita; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Angelina Ambarita, 1201134897. Adviser : Dadang Mashur, S.Sos, M.SiExhibition of job expo represent one of the way of government for facility and bring into contact searcher work with consumer of labour, assisting searcher work to get work as according to talent; enthusiasm; education and its skill. Assisting company of consumer of labour to get labour with quality; professional and skillful as according to requirement of company, and lessen unemployment number in town of pekanbaru. But practically output of is amount of location of labour of this exhibition do not reach according to goals so that can’t lessen the amount of unemployment exist in town of pekanbaru, besides down it of amount of company following exhibition of job expo in the year 2015 show that seeking of vacancy not be executed better, other problem which faced from exhibition of job this expo is the amount of searcher of ill assortedjob with available vacancy and to the number of searcher of job which is minim of skill and also elector. Target of this research is to know exhibition effectiveness of job expo by on duty town labour of pekanbaru and to know factors influencing. Theory concept the used is effectiveness which is opinion by duncan explaining there is 3 effectiveness criterion that is attainment of target, adaptation and integration. this research use research method qualitative with data study descriptively. In data collecting of writer use interview technique, documentation and observation. by using informan key as source of technique and information triangulat as data validity.Result of research which is writer conduct that exhibition effectiveness of job expo by on duty town labour of pekanbaru less effective this matter is seen from attainment of is intention of quantitative target; amount of company which only followed 65 location goals and company which do not reach, while for conducted by integration isdisnaker in conducting communications with company exist in town of pekanbaru not maksimal, and adaptation expected from charging workers through company quite effective but not been able to reduce unemployment in pekanbaru. besides factors influencing exhibition of job this expo is human resource, fund and coordination.Keywords: effectiveness, job expoKeyword: effectiveness, job expo